Shoreline Change Dynamics using Digital Shoreline Analysis System in Cemara Besar Island - Muhammad Ramdhan; Yulius Yulius; Nur Kholik (Pusat Riset Kelautan, 2020)
This paper will describe a study to find out the shoreline changes that occurred on Cemara Besar Island along with the accretion and abrasion. Data taken from the images were obtained through google earth as a result of radiometry and geometry correction from Landsat satellites in the last of 5 years. Wind data were obtained from ECMWF (European Centre for Medium-range Weather Forecasts) interm every season for 5 years. Analysis of shoreline changes was carried out using the DSAS (Digital Shoreline Analysis SYSTEM) method and analyzed by wind and sea wave factors involved in each season. The results of the analysis obtained LRR (Linear Regration Rate) and EPR (End Point Rate) values for 5 years, the extent of changes in island land mass, the value of Hs and Ts from the results of wave forecasting using wind data. To simplify the analysis, Cemara Besar Island is divided into 9 segments based on variations in LRR values. The results show that in general Cemara Besar Island have very high accretion rate in segments A, B and E with an average of 3.61 m/year or 5 years and very high abrasion occurred in segment F with an average of -1.01 m. Abrasion occurs with the greatest speed of change in segment A with an average of 4.64 m/year and the largest accretion rate in segment F with an average of -1.21791 m/year. Analysis of oceanographic factors through Wave forecasting data shows that in the west and transition I season, the significant waves height occur with Hs 1.21 m, greater than the eastern season and transition II season with Hs 0.91 m. Dominant wind direction from north (377.50 in west season and transition I, and from east direction (67,25 degre) in east season and transition I season. Wind-wave propagate according to wind direction and it will be deformed when entering shallow coastal waters. Then affects sediment transport which produces accretion and abrasion on the Cemara Besar Island.